Inequalities in the Distribution of Childhood Adversity From Birth to 11 Years - O'Connor, Meredith; Slopen, Natalie; Becares, Laia; Burgner, David; Williams, David R; Priest, Naomi (My University, 2020)
Exposure to early adversity carries long term harmful consequences for children's health and development. This study aims to 1) estimate the prevalence of childhood adversity for Australian children from infancy to 10-11 years, and 2) document inequalities in the distribution of adversity according to socioeconomic position (SEP), Indigenous status, and ethnicity. Adversity was assessed every 2 years from 0-1 to 10-11 years in the nationally representative birth cohort of the Longitudinal Study of Australian Children (N = 5107). Adversity included legal problems; family violence; household mental illness; household substance abuse; harsh parenting; parental separation/divorce; unsafe neighborhood; family member death; and bullying (from 4 to 5 years). Adversities were examined individually and summed for a measure of multiple adversity (2+ adverse experiences). By 10-11 years, 52.8% (95% confidence interval [CI] 51.0-54.7) of children had been exposed to 2 or more adversities. When combined with low SEP, children from ethnic minority and from Indigenous backgrounds had 4 to 8 times the odds of exposure to 2 or more adversities than children from higher SEP Anglo-Euro backgrounds, respectively (odds ratio [OR] 4.3, 95% CI 2.8-6.6 and OR 8.1, 95% CI 4.4-14.8). Ethnic minority and Indigenous children from higher SEP backgrounds had increased odds of exposure to multiple adversity than similarly advantaged Anglo-Euro children (OR 1.8, 95% CI 1.4-2.3 and OR 2.3, 95% CI 1.3-4.3, respectively). Addressing early adversity is a significant opportunity to promote health over the life course, and reduce health inequalities experienced by marginalized groups of children.
Keywords: adverse childhood experiences; adversity; ethnicity; health equity; socioeconomic position; Disadvantage, adversity and resilience; Childhood and child development; Culture and language; Health and wellbeing; Income, wealth and finances